Tough Women and Sensitive Men. A Qualitative Study on the Representations of Femininity and Masculinity in the Police and the Army - Florenta-Larisa Simion (Petrescu) (Bulletin of the Transilvania University of Braşov: Series VII: Social Sciences, Law, 2020)
This paper brings to the fore the representations of femininity and masculinity in Romanian Police and Army, highlighting types of speech based on the opinions of people who work in those places who were interviewed and whose identity is confidential. The police and also the Army have a militarized environment based on strict rules. My objective is to find out if the stereotypes of women and men exist and if discrimination is perceived based on their experiences.